Evaluation of a guided continuous quality improvement program in community pharmacies - Chinthammit, Chanadda (J Pharm Policy Pract, 2017)
BACKGROUND: The importance of creating and sustaining a strong culture of patient safety has been recognized as a critical component of safe medication use. This study aims to assess changes in attitudes toward patient safety culture and frequency of quality-related event (QRE) reporting after guided implementation of a continuous quality improvement (CQI) program in a panel of community pharmacies in the United States (U.S.). METHODS: Twenty-one community pharmacies volunteered to participate in the project and were randomly assigned to intervention or control groups. Pharmacy staff in the intervention group received guided training to ensure full implementation of a CQI program while those in the control group partially implemented the program. Pharmacy staff in both groups completed retrospective pre-post safety culture questionnaires and reported medication errors and near misses that occurred in their practices. Rasch analysis was applied to assess questionnaire validity and reliability and to confirm if the ordinal level data approximated interval level measures. Paired t-tests and repeated measure analysis of covariance tests were subsequently used to compare observed changes in the attitudes of subjects and frequency of QREs reporting in intervention and control groups. RESULTS: Sixty-nine employees completed the questionnaire, a 43.9% response rate. Improvement in attitudes toward patient safety was statistically significant in the intervention group in six domains: staff, training, and skill (p = 0.017); patient counseling (p = 0.043); communication about mistakes (p < 0.001); response to mistakes (p < 0.001); organizational learning – continuous improvement (p < 0.001); and overall patient safety perceptions (p = 0.033). No significant differences were observed in QRE reporting rates between intervention and control groups. However, differences were observed in the types of QREs reported (e.g., incorrect safety cap) and the point in the prescription processing workflow where a QRE was detected (e.g., partner check station, and drug utilization review station) in the intervention group (p < 0.001). CONCLUSION: Guided CQI program implementation increased the self-reported patient safety culture attitudes among staff. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40545-017-0114-x) contains supplementary material, which is available to authorized users.